The Debt-Equity Ratio Choice: Risk Sharing Instruments, A Viable Alternative - Muhammad Ahmad, Shamsuddeen; Wan Omar, Wan Ahmad Bin; Mat Junoh, Mohd Zukime Bin (IKONOMIKA, 2018)
Evidence has been documented in the literature that the interest based debt financing system is experiencing continuous discomfort. The outcome of the 2008 global financial crisis has further create fresh vigor to the assertion. Also, these authors have submitted that debt and leveraging are the two major causes of financial instability in the present system. This paper claims that the existence of the interest-based debt regime is becoming less acceptable, as excessive debt can affect the whole economic system, even in a developed country like United States. From an economic viewpoint, therefore, by banning interest rate-based contracts and decreeing exchange contracts, Islamic financeinspires risk sharing and prohibits risk transfer, risk shedding, and risk shifting. The paper proposes risk sharing based Islamic financing as a suitable alternative to the interest based debt financing. This study concludes that risk-sharing finance has several benefits, especially its potential to minimize, if not circumvent, the debt prompted financial crises that have beset the world..Keywords :  Debt-Equity Ratio; Risk Sharing Instruments; Islamic Finance